Pharmacological Rescue of the Brain Cortex Phenotype of Tbx1 Mouse Mutants: Significance for 22q11.2 Deletion Syndrome - Favicchia, Ilaria; Flore, Gemma; Cioffi, Sara; Lania, Gabriella; Baldini, Antonio; Illingworth, Elizabeth (Frontiers in Molecular Neuroscience, 2021)
Objectives Tbx1 mutant mice are a widely used model of 22q11.2 deletion syndrome (22q11.2DS) because they manifest a broad spectrum of physical and behavioral abnormalities that is similar to that found in 22q11.2DS patients. In Tbx1 mutants, brain abnormalities include changes in cortical cytoarchitecture, hypothesized to be caused by the precocious differentiation of cortical progenitors. The objectives of this research are to identify drugs that have efficacy against the brain phenotype, and through a phenotypic rescue approach, gain insights into the pathogenetic mechanisms underlying Tbx1 haploinsufficiency. Experimental Approach Disease model: Tbx1 heterozygous and homozygous embryos. We tested the ability of two FDA-approved drugs, the LSD1 inhibitor Tranylcypromine and Vitamin B12, to rescue the Tbx1 mutant cortical phenotype. Both drugs have proven efficacy against the cardiovascular phenotype, albeit at a much reduced level compared to the rescue achieved in the brain. Methods In situ hybridization and immunostaining of histological brain sections using a subset of molecular markers that label specific cortical regions or cell types. Appropriate quantification and statistical analysis of gene and protein expression were applied to identify cortical abnormalities and to determine the level of phenotypic rescue achieved. Results Cortical abnormalities observed in Tbx1 mutant embryos were fully rescued by both drugs. Intriguingly, rescue was obtained with both drugs in Tbx1 homozygous mutants, indicating that they function through mechanisms that do not depend upon Tbx1 function. This was particularly surprising for Vitamin B12, which was identified through its ability to increase Tbx1 gene expression. Conclusion To our knowledge, this is only the second example of drugs to be identified that ameliorate phenotypes caused by the mutation of a single gene from the 22q11.2 homologous region of the mouse genome. This one drug-one gene approach might be important because there is evidence that the brain phenotype in 22q11.2DS patients is multigenic in origin, unlike the physical phenotypes, which are overwhelmingly attributable to Tbx1 haploinsufficiency. Therefore, effective treatments will likely involve the use of multiple drugs that are targeted to the function of specific genes within the deleted region.